Detection of sexually transmitted pathogens Trichomonas vaginalis and Herpes simplex virus in women - Dalya Basil Hanna; Arwa Mujahid Abdullah Al-Shuwaikh; Zahraa Qasim Ali (College of Pharmacy / Mustansiriyah University, 2019)
There are more than 340 million new cases of sexually transmitted infections (STIs) occurred annually throughout the world, the highest incidence is in people of developing countries. Pelvic inflammation, sterility, ectopic pregnancy, morbidity and mortality of newborns, and genital carcinoma have been assumed to be related to STIs. Sexually transmitted diseases have various clinical symptoms while 70% gonococcal or non-gonococcal urethritis in males and genital tract infections in females are asymptomatic, both symptomatic and asymptomatic infections may cause severe complications, previous studies revealed that wide range of pathogens recognized as a causative agents of urethritis in males and genital tract infections in females, such as Trichomonas vaginalis and herpes simplex virus. More epidemiological studies are needed to evaluate the significant role of organisms other than the recognized genital pathogens in vaginal syndromes. In summary we conclude that sexually transmitted diseases may increase reproductive morbidity rate causing difficulties in conception especially the infection with T. vaginalis and herpes simplex viruses, so concentrating on different methods in diagnosis is required. In addition, the cost and time of the test should be taken in consideration.